2019
DOI: 10.1080/10530789.2018.1563267
|View full text |Cite
|
Sign up to set email alerts
|

How is participation related to well-being of homeless people? An explorative qualitative study in a Dutch homeless shelter facility

Abstract: The majority of homeless people is socially excluded which negatively affects their well-being. Therefore, participation-based programs are needed. The current research is conducted within a Dutch homeless shelter facility that offers educational, recreational, and labor activities to clients in an environment which is designed to feel safe (an enabling niche). The main aim of these activities is to facilitate social participation. We conducted two qualitative studies consisting of 16 semi-structured interview… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…In the current study we did not evaluate the quality and the content of the activities, which means that we cannot draw a conclusion on this. However, in another qualitative study that was conducted in the same shelter facility we found that participation in activities in the shelter improved social support, clients made new friends, developed stronger communication skills, and became more social and helpful (Rutenfrans-Stupar et al 2019). Finally, we could not confirm the relationship between age and social participation (i.e., we expected that the older the clients are, the lower their social participation rate would be).…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…In the current study we did not evaluate the quality and the content of the activities, which means that we cannot draw a conclusion on this. However, in another qualitative study that was conducted in the same shelter facility we found that participation in activities in the shelter improved social support, clients made new friends, developed stronger communication skills, and became more social and helpful (Rutenfrans-Stupar et al 2019). Finally, we could not confirm the relationship between age and social participation (i.e., we expected that the older the clients are, the lower their social participation rate would be).…”
Section: Discussionmentioning
confidence: 73%
“…Self-esteem was assessed using the ten-item 'Rosenberg Self-Esteem Scale' (RSES) (Rosenberg 1965;Van Der Linden et al 1983). Examples of items include 'On the whole, I am satisfied with myself', and 'I certainly feel useless at times'.…”
Section: Well-beingmentioning
confidence: 99%
“…The results relating to the play dimension are also interesting, since Rutenfrans-Stupar et al [70] noted the recreational benefits of employment for homeless people in building a sense of belonging, attachment and connection to the community. Although another study on homelessness and employment noted the difficulties employers had in providing such opportunities [41], it also reported that homeless people reported social activities such as football as an important way to engage in mainstream society and avoid harmful substance use.…”
Section: Discussionmentioning
confidence: 96%
“…40 For a variety of reasons pertinent to particular studies, the use of non-verbatim transcripts has been an approach selected by scholars conducting qualitative research. [37][38][39][40][41] As is often the case in qualitative research, in this study the researchers were the "tools" used to analyze data. We were therefore aware of the potential for preconceptions to be introduced during data analysis.…”
Section: Discussionmentioning
confidence: 99%